Dance Movement Therapy with Children: Practical Aspects of Remote Group Work - Einat Shuper-Engelhard; Maya Vulcan (MDPI AG, 2022)
The global COVID-19 outbreak has forced psychotherapists to find creative ways to continue treating their clients from afar. Dance movement therapy emphasizes the body-mind connection and offers a unique mode of emotional intervention for supporting mental processes. The present study is the first to examine the distinctive qualities of group dance movement therapy in the context of remote emotional intervention with young children. Fourteen preschool children participated in six DMT meetings. The data generated three themes: 1. play as a platform for transforming technical complexity into an expression of the inner world; 2. accessories and props as means of motivation for movement and imaginative play; 3. playfulness-inhibiting conditions in settings of remote therapy. The discussion examines the significance of bodily expressions in remote therapy for understanding the needs of children in times of crisis and for getting acquainted with feelings and sensations which do not lend themselves easily to verbal expression.